Developmental and Crosslinguistic Perspectives in Learner Corpus Research. - Tono, Yukio (Tokyo University of Foreign Studies., 2012)
This volume provides a state-of-the-art overview of current research and developments on the use of learner corpora perceived from developmental and crosslinguistic perspectives. The book is divided into two parts. The eleven contributions of Part I investigate the development of English language skills of young learners across seven countries/regions on the basis of a new corpus resource called the International Corpus of Crosslinguistic Interlanguage (ICCI). Part II contains seven papers devoted to other varieties of learner corpora, especially spoken learner corpora and learner corpora of l.